Innovation in English Language Learning Assessment in Class VII of SMP Negeri 1 Dolok Merawan: Development of a HOTS-Based Evaluation Tool with the Help of Wordwall - Nurul Aprilia Yusri; Abdul Hasan Saragih; Naeklan Simbolon (RIRAI Publisher, 2024)
An evaluation instrument or evaluation tool is a tool that meets academic requirements. The evaluation instrument still uses paper evaluation tools and does not use online learning evaluation. The aim of this research is to develop a wordwall-assisted HOTS-based English language learning evaluation tool. This type of research applies the Research and Development (R&D) research method. The subjects in this research were class VII students of SMP Negeri 1 Dolok Merawan who used the HOTS-based learning evaluation tool with the help of Wordwall, for a total of 32 students. The object of research is English-language reading material in the form of wordwall assistance. This research has been validated through stages by material experts, media experts, instructional design experts, language experts, and evaluation experts. This research has trial stages, namely initial field trials, main field trials, and operational field trials. This research also tested the effectiveness of the wordwall-assisted HOTS-based English learning evaluation tool. The research results show that students who use the HOTS-based English language learning evaluation tool assisted by Wordwall are